Some limit theorems for m-dependent random variables - Egorov, V. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. А. Егоров. Некоторые предельные теоремы для m-зависимых случайных величин V. Jegorovas. Keletas ribinių teoremų m-priklausomiems atsitiktiniams dydžiams